Queer feminist science studies : a reader - Cipolla, Cyd; Gupta, Kristina; Rubin, David A. (Feminist technosciences, 2017)
Queer Feminist Science Studies takes a transnational, trans-species, and intersectional approach to this cutting-edge area of inquiry between women's, gender, and sexuality studies and science and technology studies (STS). The essays here "queer"-or denaturalize and make strange-ideas that are taken for granted in both areas of study. Reimagining the meanings of and relations among queer and feminist theories and a wide range of scientific disciplines, contributors foster new critical and creative knowledge-projects that attend to shifting and uneven operations of power, privilege, and dispossession, while also highlighting potentialities for uncertainty, subversion, transformation, and play. Theoretically and rhetorically powerful, these essays also take seriously the materiality of "natural" objects and phenomena: bones, voles, chromosomes, medical records and more all help substantiate answers to questions such as, What is sex? How are race, gender, sexuality, and other systems of differences co-constituted? The foundational essays and new writings collected here offer a generative resource for students and scholars alike, demonstrating the ingenuity and dynamism of queer feminist scholarship.